TINJAUAN TERHADAP PENYELESAIAN KREDIT MACET PADA ASTRA CREDIT COMPANIES (ACC) PEKANBARU MELALUI JASA PIHAK KETIGA (PROFESIONAL COLLECTOR) - Putri Maya Sari; Maryati Bachtiar; Dasrol ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Regulation about professional collectors can be observed on 49 section No. 30/POJK.05/2014 Good Corporate Governance For Finance Companies. If the regulation is not applied, professional collectors became illegal, and their actions also be illegal too. The purpose is : First, The Completion Of Non Performing Loan By Professional Collectors in Astra Credit Companies (ACC) Pekanbaru Based On The Legislation, Second, Astra Credit Companies (ACC) Pekanbaru’s Responsibility Toward Professional Collectors On Their Companies For Completion Non Performing Loan.The kind of the research is empiric, the research be held on location to get the real result. The location is Astra Credit Companies (ACC) Pekanbaru office, the population and sample is the people who get involved with this research, data source is primary data, secondary data and tertiary data, data collection techniques is interview and related literature.The conclusion of the research result is had two points. First, the completion non performing loan by professional collectors not according the legislation yet. Second, Astra Credit Companies (ACC) Pekanbaru must take full responsibility and make sure customers not harmed. The advice is, First, Astra Credit Companies (ACC) Pekanbaru must keep up the regulation, Second, Astra Credit Companies (ACC) Pekanbaru have to make sure to take full responsibility and the customers not harmed.Key Words: Non Performing Loan - The Third Side - Professional Collector